2014
DOI: 10.1128/jvi.03355-13
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 16 E6* Induces Oxidative Stress and DNA Damage

Abstract: High-risk types of human papillomavirus (HPV) are the causative agents of virtually all cases of cervical cancer and a significant proportion of other anogenital cancers, as well as both oral and pharyngeal cancers. The high-risk types encode two viral oncogenes, E6 and E7, which work together to initiate cell transformation. Multiple steps involving the activities and interactions of both viral and cellular proteins are involved in the progression from HPV infection to cell transformation to cancer. The E6 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
140
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(148 citation statements)
references
References 49 publications
8
140
0
Order By: Relevance
“…This because ROS can promote the DNA oxidation, leading to DNA breaks [5] observed in papillomavirus-infected cells lines (table 1, figure 7), as well as those described in literature [10][11][12][13][14]19]. Similar results were also verified in HPV infected cells, in which it was demonstrated that the HPV-16 E6*-induced oxidative stress and DNA breaks, which are necessary to HPV integration [15,16]. Based on these data, we analyzed the action of BPV-1 E6 recombinant oncoprotein in glycolytic metabolism.…”
Section: Discussionsupporting
confidence: 73%
“…This because ROS can promote the DNA oxidation, leading to DNA breaks [5] observed in papillomavirus-infected cells lines (table 1, figure 7), as well as those described in literature [10][11][12][13][14]19]. Similar results were also verified in HPV infected cells, in which it was demonstrated that the HPV-16 E6*-induced oxidative stress and DNA breaks, which are necessary to HPV integration [15,16]. Based on these data, we analyzed the action of BPV-1 E6 recombinant oncoprotein in glycolytic metabolism.…”
Section: Discussionsupporting
confidence: 73%
“…However, BPV-infected cells do not reduce the ROS production, even after malignant transformation. Although controversial, these data can be attributed to E6 oncoprotein, which reduces SOD2 expression levels, increasing ROS formation [145]. This action increase the pro-oxidant stimulus (ROS production) and reduces the anti-oxidant cell capability (SOD2), leading to oxidant stress.…”
Section: Oncogenic Virus and Ros Generation: A Field To Explorementioning
confidence: 97%
“…[85] Additionally, ROS activates HPV [16] and its E6 protein can in turn cause production of more ROS and DNA damage. [86] The E2 protein of HPV also results in production of ROS by interacting with the cells' mitochondria [87] creating oxidized cytosines that can spontaneously deaminate and become thymines. Cytosine to thymine transition mutations can also occur via viral activation of the APOBEC system resulting in epigenetic methylation and deamination of cytosines.…”
Section: Discussionmentioning
confidence: 99%